PATHOPHYSIOLOGICAL JUSTIFICATION OF THE USE OF OZONE THERAPY IN THE COMPLEX TREATMENT OF PATIENTS WITH HEMORRHOIDAL DISEASE - Лидия Евгеньевна Бубнова; Наталья Викторовна Алексеева; Леонид Николаевич Иванов; Дмитрий Николаевич Бубнов; Александр Аринариевич Юсов (Медицина в Кузбассе, 2024)
The purpose of the study – to evaluate the possibility of improving the basic therapy of hemorrhoidal disease, the effectiveness of pathogenetic treatment and the dynamics of clinical and biochemical rheological, immunological parameters in combination with intravenous parenteral ozone therapy. Materials and methods. Тhe patients were divided into two groups. The main group included 33 patients who underwent hemorrhoidectomy according to the generally accepted technique on the «Surgitron» device in combination with parenteral ozone therapy with an ozone content at the outlet of the device 1600 mcg/l sol. NaCI 0.9% – 200.0 ml intervenous drip daily for 1week. The control group included 31 patients who underwent hemorrhoidectomy without ozone therapy. Results. The presence of a pathogenetic relationship between the severity of clinical manifestations of hemorrhoidal disease and the degree of increase in the content of MWM in the blood allows us to recommend this test as an objective criterion for assessing the severity of the disease. In our observations, the clinical and laboratory manifestations of endogenous intoxication decreased. Ozonoterapy contributed to the improvement of microcirculation and increased rheological properties of blood. The fibrinolytic activity of the blood decreased and the thrombin time lengthened. Immune resistance has normalized, antioxidant protection has activated, and the intensity of pain syndrome in patients with this pathology has decreased. Conclusion. Ozone therapy has a detoxifying effect, strengthens the immune system, and reduces blood microviscosity. Thus, the reserve capabilities of the body increase with the effectiveness of potentiation of basic therapy by parenteral administration of an ozonated solution.